2008
DOI: 10.1128/jb.01667-07
|View full text |Cite
|
Sign up to set email alerts
|

Cel9D, an Atypical 1,4-β- d -Glucan Glucohydrolase from Fibrobacter succinogenes : Characteristics, Catalytic Residues, and Synergistic Interactions with Other Cellulases

Abstract: The increasing demands of renewable energy have led to the critical emphasis on novel enzymes to enhance cellulose biodegradation for biomass conversion. To identify new cellulases in the ruminal bacterium Fibrobacter succinogenes, a cell extract of cellulose-grown cells was separated by ion-exchange chromatography and cellulases were located by zymogram analysis and identified by peptide mass fingerprinting. An atypical family 9 glycoside hydrolase (GH9), Cel9D, with less than 20% identity to typical GH9 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 33 publications
(33 reference statements)
1
49
1
Order By: Relevance
“…Located between the two modules are three carbohydrate-binding modules (CBMs). GH9 family enzymes have an (␣/␣) 6 -barrel fold, and this family of enzymes is known to contain members that exhibit different enzymatic activities, including endoglucanase (45), cellobiohydrolase (15), 1,4-␤-D-glucan glucohydrolase (43), ␤-glucosidase (40), and exo-␤-glucosaminidase (23). The GH5 family of enzymes have an (␤/␣) 8 -barrel fold, and this family also encodes diverse enzymatic activities, including endoglucanase (16), mannanase (20), mannosidase (20), xylanase (14), chitosanase (50), glucosidase (11), licheninase (25), fucosidase (61), galactanase (44), endoglycoceramidase (9), and mannan transglycosylase (6).…”
mentioning
confidence: 99%
“…Located between the two modules are three carbohydrate-binding modules (CBMs). GH9 family enzymes have an (␣/␣) 6 -barrel fold, and this family of enzymes is known to contain members that exhibit different enzymatic activities, including endoglucanase (45), cellobiohydrolase (15), 1,4-␤-D-glucan glucohydrolase (43), ␤-glucosidase (40), and exo-␤-glucosaminidase (23). The GH5 family of enzymes have an (␤/␣) 8 -barrel fold, and this family also encodes diverse enzymatic activities, including endoglucanase (16), mannanase (20), mannosidase (20), xylanase (14), chitosanase (50), glucosidase (11), licheninase (25), fucosidase (61), galactanase (44), endoglycoceramidase (9), and mannan transglycosylase (6).…”
mentioning
confidence: 99%
“…Since the initial report of a C-terminal basic domain (BTD), specific to enzymes in F. succinogenes (32), many BTDs in this strain have been reported (22,37,38). To date, the role of the BTDs remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Our simulations involving three characterised enzymes from F. succinogenes S85 showed synergies between the endoglucanase Cel51A and the exocellulase Cel9D, in terms of increased activity on glucosidic bonds. Qi et al [69] found Cel51A and Cel9D showed in vitro synergies when degrading crystalline cellulose, compared with Cel51A alone. Our simulation result cannot be compared quantitatively with this result since the substrate being degraded differed.…”
Section: Considerationsmentioning
confidence: 99%
“…The first two enzymes were Cel51A and Cel9D, which have been characterised and shown to act synergistically [69,70]. Cel51A is an endoglucanase that acts on cellulose, but also (1,3;1,4)-β-glucans and xyloglucans mainly producing oligosaccharides with a DP of 2-5.…”
Section: Simulation Of Enzymatic Actionmentioning
confidence: 99%